2011
DOI: 10.1158/1535-7163.mct-10-1108
|View full text |Cite|
|
Sign up to set email alerts
|

Carfilzomib Interacts Synergistically with Histone Deacetylase Inhibitors in Mantle Cell Lymphoma Cells In Vitro and In Vivo

Abstract: Interactions between the proteasome inhibitor carfilzomib and the HDAC inhibitors vorinostat and SNDX-275 were examined in mantle cell lymphoma (MCL) cells in vitro and in vivo. Co-administration of very low, marginally toxic carfilzomib concentrations (e.g., 3–4 nM) with minimally lethal vorinostat or SNDX-275 concentrations induced sharp increases in mitochondrial injury and apoptosis in multiple MCL cell lines and primary MCL cells. Enhanced lethalitly was associated with JNK1/2 activation, increased DNA da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 47 publications
11
64
0
Order By: Relevance
“…In the present study, the co-administration of VPA with PI, MG132, PI-1 or PR-39 induced a marked increase in apoptosis in human colorectal cancer cells. Our results are consistent with those reported by other groups using several different cell systems and various combinations of HDACIs and PIs (1,15,22,35,39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the co-administration of VPA with PI, MG132, PI-1 or PR-39 induced a marked increase in apoptosis in human colorectal cancer cells. Our results are consistent with those reported by other groups using several different cell systems and various combinations of HDACIs and PIs (1,15,22,35,39).…”
Section: Discussionsupporting
confidence: 93%
“…Co-administration of the antioxidant, L-NAC, (15 mM) substantially blocked the VPA/PI-mediated increase in ROS levels (data not shown). Our results are consistent with those of other studies using different combinations of HDACs and PIs in various cell systems (15,35). HDACIs have been shown to raise intracellular ROS levels (36), and our results indicated that the combination of VPA and PIs induced a greater increase in ROS levels than that observed with either agent alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Proteasome inhibitor, marizomib in combination with vorinostat or entinostat increased apoptosis in several leukemia cells, caspase 8 activation and oxidative stress contributed to the synergistic effects 45 . In vitro and in vivo studies with diffuse large B cell lymphoma and mantle cell lymphoma cells including bortezomib resistant ones showed that another proteasome inhibitor, carfilzomib, increased the effects of vorinostat 76,77 . 5) Numerous studies show synergisms or additive effects combining the HDAC inhibitors and DNAdamaging agents such as topoisomerase inhibitors, DNAintercalators, inhibitors of DNA synthesis and agents covalently modifying DNA (i.e.…”
Section: ) Promising Results Have Been Reported For Combinations Of mentioning
confidence: 99%
“…29 This can be abrogated by HDAC6 mediated targeting of these proteins to aggresomes with resulting degradation through activation of autophagy. There is therefore a considerable rationale in combining an HDAC inhibitor with a proteasome inhibitor 30,31 and trials in PTCL are ongoing.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%